Versatile energy loss conversion for recovering waste alternating potential through polarization transfer medium. (March 2020) - Yong, Hyungseok; Heo, Deokjae; Kim, Banseok; Moon, Haksung; Choi, Kyungwho; Kim, Dongseob; Lee, Sangmin
Abstract: Electric energy is considered the most acceptable solution to address environmental issues and energy shortage. However, the widespread generation and consumption of electric energy on a global scale increase a significant amount of unrecognised and unintentionally wasted electrical energy from a microscopic to macroscopic scale in electrical systems, or even by the movements of the human body in daily life. However, no fundamental solution has yet been proposed for harvesting these energy losses. Here, we first introduce an intuitive and innovative concept, called the Versatile Energy-Loss Conversion (VELC), which recovers waste AC energy occurring in electrical systems and daily life. Our fundamental research is demonstrated successfully through standardised electrical experiments, electrostatic simulations, and complementary analysis. Furthermore, the results of the demonstration of VELC in electrical systems and daily life indicate the possibility of this scientific research to improve the quality of life in human civilisation at large. Graphical abstract: Image 1 Highlights: Innovative and intuitive energy loss conversion method, called Versatile Energy Loss Conversion (VELC), is suggested. VELC can easily recover the waste AC energy form AC/DC electronics and be applied to various applications. VELC can recover the waste AC energy from human body motion via wireless contact. All energy losses from different sources of different forms and sizes can be recovered via one device, i. e. the VELC system.